Food Insufficiency, Depression, and the Modifying Role of Social Support: Evidence from a Population-Based, Prospective Cohort of Pregnant Women in Peri-Urban South Africa - Tsai, Alexander C. (Soc Sci Med, 2016)
RATIONALE: Food insecurity has emerged as an important, and potentially modifiable, risk factor for depression. Few studies have brought longitudinal data to bear on investigating this association in sub-Saharan Africa. OBJECTIVE: To estimate the association between food insufficiency and depression symptom severity, and to determine the extent to which any observed associations are modified by social support. METHODS AND RESULTS: We conducted a secondary analysis of population-based, longitudinal data collected from 1,238 pregnant women during a three-year cluster-randomized trial of a home visiting intervention in Cape Town, South Africa. Surveys were conducted at baseline, 6 months, 18 months, and 36 months (85% retention). A validated, single-item food insufficiency measure inquired about the number of days of hunger in the past week. Depression symptom severity was measured using the Xhosa version of the 10-item Edinburgh Postnatal Depression Scale. In multivariable regression models with cluster-correlated robust estimates of variance, lagged food insufficiency had a strong and statistically significant association with depression symptom severity (β=0.70; 95% CI, 0.46-0.94), suggesting a 6.5% relative difference in depression symptom severity per day of hunger. In stratified analyses, food insufficiency had a statistically significant association with depression among women with low levels of instrumental support. Using quantile regression, we found that the adverse impacts of food insufficiency were experienced to a greater degree by women in the upper end of the conditional distribution of depression symptom severity. Estimates from fixed-effects regression and fixed-effects quantile regression, accounting for unobserved confounding by time-invariant characteristics, were similar. CONCLUSIONS: Food insufficiency was associated with depression symptom severity, particularly for women in the upper end of the conditional depression distribution. Instrumental social support buffered women against the adverse impacts of food insufficiency.